Instrument Effect on the Activated Protein C Resistance Plasma Assay Performed by a Commercial Kit - De Stefano, V; Paciaroni, K; Mastrangelo, S; Rutella, S; Bizzi, B; Leone, G (Thrombosis and Haemostasis, 1996)
In order to evaluate the influence of the coagulation instrument on the activated protein C (APC)-resistance plasma assay performed by a commercial kit, we tested 70 plasma samples on 4 different instruments during a simultaneous session run using a same lot of Coatest APC-resistance (Chromogenix). The results were analyzed employing three different modes of expression (aPTT prolongation in the presence of APC, APC-sensitivity ratio, normalized APC-sensitivity ratio) and three different diagnostic threshold values (below the control mean −2 standard deviations or the lowest control value or the 5th percentile of the control values). The inter-instruments variability in the mean values of the control individuals can be limited expressing the results as nor-malized-APC-sensitivity ratio (range 0.99-1.05). The overall diagnostic yield in thrombotic patients and their relatives depended mainly on the instrument employed and only in some cases on the mode of expression of the results and on the diagnostic threshold value. The sensitivity of the commercial assay on heterozygotes for factor V Leiden diagnosed by gene analysis was overall satisfactory (75-100%) but in some cases a lower diagnostic yield was noticed, depending on the type of instrument employed and/or the type of expression of the results and/or the diagnostic threshold values. Thus the instrument system adopted should be carefully considered in the interpretation of the results using the commercial kit.